Calcineurin homologous protein isoform 2 supports tumor survival via the sodium hydrogen exchanger isoform 1 in non-small cell lung cancer - Wayne Taylor Cottle; Clarice Hayley Wallert; Kristine Kay Anderson; Michelle Fang Tran; Clare Loraine Bakker; Mark Anthony Wallert; Joseph John Provost (Tumor Biology)
Maintaining intracellular pH is crucial for preserving healthy cellular behavior and, when dysregulated, results in increased proliferation, migration, and invasion. The Na + /H + exchanger isoform 1 is a highly regulated transmembrane antiporter that maintains pH homeostasis by exporting protons in response to intra- and extracellular signals. Activation of Na + /H + exchanger isoform 1 is exquisitely regulated by the extracellular environment and protein cofactors, including calcineurin B homologous proteins 1 and 2. While Na + /H + exchanger isoform 1 and calcineurin B homologous protein 1 are ubiquitously expressed, calcineurin B homologous protein 2 shows tissue-specific expression and upregulation in a variety of cancer cells. In addition, calcineurin B homologous protein 2 expression is modulated by tumorigenic extracellular conditions like low nutrients. To understand the role of calcineurin B homologous protein 2 in tumorigenesis and survival in lung cancer, we surveyed existing databases and formed a comprehensive report of Na + /H + exchanger isoform 1, calcineurin B homologous protein 1, and calcineurin B homologous protein 2 expression in diseased and non-diseased tissues. We show that calcineurin B homologous protein 2 is upregulated during oncogenesis in many adeno and squamous carcinomas. To understand the functional role of calcineurin B homologous protein 2 upregulation, we evaluated the effect of Na + /H + exchanger isoform 1 and calcineurin B homologous protein 2 depletion on cellular function during cancer progression in situ. Here, we show that calcineurin B homologous protein 2 functions through Na + /H + exchanger isoform 1 to effect cell proliferation, cell migration, steady-state pH i , and anchorage-independent tumor growth. Finally, we present evidence that calcineurin B homologous protein 2 depletion in vivo has potential to reduce tumor burden in a xenograft model. Together, these data support the tumor-promoting potential of aberrant calcineurin B homologous protein 2 expression and position calcineurin B homologous protein 2 as a potential therapeutic target for the treatment of non-small cell lung cancer.